2022
DOI: 10.1183/16000617.0076-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of home-based pulmonary rehabilitation: systematic review and meta-analysis

Abstract: IntroductionDespite proven effectiveness for people with chronic respiratory diseases, practical barriers to attending centre-based pulmonary rehabilitation (centre-PR) limit accessibility. We aimed to review the clinical effectiveness, components and completion rates of home-based pulmonary rehabilitation (home-PR) compared to centre-PR or usual care.Methods and analysisUsing Cochrane methodology, we searched (January 1990 to August 2021) six electronic databases using a PICOS (population, intervention, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Despite the proven benefits and numerous guideline recommendation supporting PR as a means of improving physical and psychological wellbeing of people with chronic respiratory disease, PR remains severely underused. 24 Inconvenient timing of programs and geographical distance to PR centers (center-PR) are commonly reported as barriers, in high, low-/middle-income countries. 24 There has been a recent movement to provide PR services remotely in hopes of improving attendance and completion, and the ongoing SARS CoV-2 pandemic has only served to propel this movement.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the proven benefits and numerous guideline recommendation supporting PR as a means of improving physical and psychological wellbeing of people with chronic respiratory disease, PR remains severely underused. 24 Inconvenient timing of programs and geographical distance to PR centers (center-PR) are commonly reported as barriers, in high, low-/middle-income countries. 24 There has been a recent movement to provide PR services remotely in hopes of improving attendance and completion, and the ongoing SARS CoV-2 pandemic has only served to propel this movement.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…Future trials addressing issues of uptake, engagement, completion, and attrition may provide more clarity on which patients would benefit most from home-PR, allowing health care workers to "target" certain patients for home versus center PR. 24…”
Section: Clinical Relevancementioning
confidence: 99%
“…Digital interventions have shown some promise at increasing completion rates,49 however, improvements in important outcomes such as walking capacity are less convincing. Two systematic reviews have demonstrated broadly equivalent results in unsupervised exercise training and home based PR for those with COPD 50 51. However, all interventions should consider the key components of PR 52…”
Section: Improving Uptake Of Pulmonary Rehabilitation: a Patient-cent...mentioning
confidence: 99%
“…It is important, however, for patients with CRDs to have continued access to PR despite lockdown periods 8 and there is now strong evidence suggesting Home-PR programme provides outcomes comparable to Centre-based PR 9,10,11,12 . Compared to usual care, our recent meta-analysis showed that Home-PR programme signi cantly improved exercise capacity [standardised mean difference (SMD) 0.88; 95% con dence interval (CI) 0.32 to 1.44; p = 0.002) and HRQoL (SMD − 0.62; 95% CI -0.88 to -0.36; p = 0.001)] 13 . Hence a Home-PR programme enables people with CRDs to continue receiving rehabilitation even if they are unable to attend the PR centre for whatever reason.…”
Section: Introductionmentioning
confidence: 99%